Upaya (Hukum) Termohon Ikrar Talak yang Tidak Ditalak dalam Persidangan Pengadilan Agama - Ahmad Khairun H (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
In divorce cases, the absence of the respondent or wife has no effect on the exercise of the talaq pledge, talaq pledge can still be carried out even if the respondent or wife is not present. But conversely, the absence of a husband in a divorce trial as Petitioner pronunciation divorce pledge has legal implications extraordinary. Article 70 paragraph (6) of the Law on Religious Courts asserted that without the presence of the husband in the trial pronunciation pledge divorce causes a court decision religion that had permanent legal force becomes null and void and has implications for the status of marriage between the Petitioner and the Defendant remains valid and binding as normal. The absence of the rule of law that can be coercive power for the Petitioner to carry out the verdict, it does not negate the legal remedies that can be done by the wife as a defendant to fulfill his legal rights. Legal remedies that can be dane include 1) Telling on neglect that happened to the authorities by using laws instruments of domestic violence elimination, 2) filing for divorce, as in general, 3) applying for judicial review to the Constitutional Court, or 4) applying for the execution of the content of the pledge decision/determination of divorce case to the religious court.